COVID-19 LABORATORY DIAGNOSIS: CURRENT PROBLEMS AND DIFFICULTIES - Abdualwahab Mohamed Madkali, Abdulaziz Dakhil saad alshahrani, Khalid Moadi Assiri Ali Abdullah Mohmmed Alkhathami, Hajar Ali Alhasani, Fareah Ali Abutalib Alhassani, Mariam Abdullah Alghamdi, Mariam Mustafa Abutalib Alhasani,; Hamad Ali Mohammed Alhayli, Mohammed Ahmed Ibrahim Alsahabi, Abdulaziz Fayez AlMoslehi, Asrar Hasan Algubishi, Salman Khloofh Alahmari (Chelonian Research Foundation, 2022)
Over the past few months, the COVID-19 outbreak has had a significant effect on clinical microbiology laboratories. This opinion discusses the difficulties that currently exist for diagnosing infections brought on by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). For a timely and precise molecular diagnosis of COVID-19 during the preanalytical stage, the appropriate respiratory tract samples must be collected at the appropriate time from the appropriate anatomic location. It takes the right precautions to ensure the safety of the laboratory personnel and to yield accurate test results. While antibody-based methods are being introduced as supplementary tools, real-time reverse transcription-PCR (RT-PCR) tests continue to be the preferred molecular test for the etiologic diagnosis of SARS-CoV-2 infection at the analytical stage. Testing results should be carefully analyzed in the postanalytical stage using both molecular and serological findings. Ultimately, rapid and accurate diagnosis and monitoring of SARS-CoV-2 infections will be made possible by random-access, integrated devices that are scalable and accessible at the point of care. These devices will also play a major role in helping to contain the outbreak. KEYWORDS: molecular testing, serology, specimen type, COVID-19, SARS-CoV-2.